Antibiotic Resistance Genes in Freshwater Trout Farms in a Watershed in Chile. Issue 5 (18th July 2019) - Bueno, Irene; Travis, Dominic; Gonzalez‐Rocha, Gerardo; Alvarez, Julio; Lima, Celia; Benitez, Cristián Garcia; Phelps, Nicholas B.D.; Wass, Britta; Johnson, Timothy J.; Zhang, Qian; Ishii, Satoshi; Singer, Randall S.
Abstract : Point sources such as wastewater treatment plants, terrestrial agriculture, and aquaculture may release antibiotic residues, antibiotic resistant bacteria, and antibiotic resistance genes (ARGs) into aquatic ecosystems. However, there is a lack of quantitative studies attributing environmental ARG abundance to specific sources. The goal of this study was to evaluate the role of freshwater trout farms in the release and dissemination of ARGs into the environment. Sediment samples upstream and downstream from five rainbow trout farms were collected over time in southern Chile. A microfluidic quantitative polymerase chain reaction approach was used to quantify an ARG array covering different mechanisms of resistance, and data were analyzed using principal component analysis (PCA) and linear mixed regression models. Surveys were also conducted to obtain information about management practices, including antibiotic use, at the farms. Florfenicol and oxytetracycline were used at these farms, although at different rates. A total of 93 samples were analyzed. In the PCA, strB, sul1, sul2, qacG, tet (A), tet (B), tet (C), tet (W), and floR grouped together. A statistically significant increase in abundance of qacG, strB, sul1, and several tet genes was found downstream from the farms compared with upstream sites, and retention ponds had the highest ARG abundance at each site. Antibiotic resistance gene levels returned to baseline at an average distance of 132.7 m downstream from the farms. Although results from this study indicate an influence of trout farms on the presence of ARGs in the immediate environment, the extent of their contribution to ARG dissemination is unknown and deserves further investigation. Core Ideas: Point sources contribute to antimicrobial resistance (AMR) in the environment. Antibiotic resistance genes (ARG) were quantified in river sediment samples. Freshwater trout farms in southern Chile increased ARG abundance in the watershed. The extent of the contribution of the trout farms on ARG dissemination is uncertain. Epidemiological methods are needed to attribute environmental AMR to specific point sources.